Pengaruh Kebijakan Dividen, Profitabilitas dan Kepemilikan Institusional Terhadap Nilai Perusahaan Diintervensi Oleh Struktur Modal - Putri, Parwanti Nuryoko; Haryati, Tantina (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The International Monetary Fund (IMF) revealed that global economic growth is declining due to inflation. The decline in economic growth has an impact on the banking sector, which plays a crucial role in maintaining economic stability. This research aims to examine and analyze the influence of dividend policy, profitability, and institutional ownership on firm value, with capital structure as an intervening variable. The objects of observation include banking sector businesses listed on the Indonesia Stock Exchange (IDX) for the period 2020 to 2024. The sampling of sample entities was carried out using a purposive sampling approach, consisting of 11 entities over a period of 5 years, resulting in a total of 55 data units. The type of data in this research uses secondary data. This research uses the Partial Least Square (PLS) approach as an evaluation tool supported by the SmartPLS version 3.0 application. The results of this research show that dividend policy and profitability influence firm value, while institutional ownership and capital structure do not. Dividend policy and profitability influence capital structure, but institutional ownership does not influence capital structure. Capital structure is unable to intervene in the relationship between the three independent variables and firm value. Based on the research results, the R-square value of the company's value is 0.500, meaning that 50% of the variation in the company's value variable can be explained by the independent variable, while the remaining 50% is influenced by other variables. The R-square of the capital structure reaches 0.479, meaning that 48% of the variation in the capital structure variable can be explained by the independent variable, while the remaining 42% is influenced by other variables.